Prediction of 30-Day Readmission After Stroke Using Machine Learning and Natural Language Processing - Lineback, Christina M.; Garg, Ravi; Oh, Elissa; Naidech, Andrew M.; Holl, Jane L.; Prabhakaran, Shyam (Frontiers in Neurology, 2021)
Background and Purpose: To determine whether machine learning (ML) and natural language processing (NLP) from electronic health records (EHR) improve the prediction of 30-day readmission after stroke. Methods: Among index stroke admissions between 2011 and 2016 at an academic medical center, we abstracted discrete data from the EHR on demographics, risk factors, medications, hospital complications, and discharge destination and unstructured textual data from clinician notes. Readmission was defined as any unplanned hospital admission within 30 days of discharge. We developed models to predict two separate outcomes: (1) 30-day all-cause readmission and (2) 30-day stroke readmission. We compared the performance of logistic regression to advanced ML algorithms. We used several NLP methods to generate additional features from unstructured textual reports. We evaluated the performance of prediction models using a 5-fold validation and tested the best model in a held-out test dataset. Area under curve (AUCs) were used to compare discrimination of each model. Results: In an held-out test dataset advanced ML methods along with NLP features outperformed logistic regression for all-cause readmission (auc 0.64 vs. 0.58, p<0.001) and stroke readmission prediction (auc 0.62 vs. 0.52, p<0.001). Conclusion: NLP-enhanced machine learning models potentially advance our ability to predict readmission after stroke. However, further improvement is necessary before implementing in clinical practice given the weak discrimination.